A survey on m-Learning of Secondary School Teachers in Greece - Kousloglou, Manolis; Nikolopoulou, Kleopatra; Hatzikraniotis, Euripides (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
The purpose of this study was to investigate the views towards m-learning, of a specific group of secondary school teachers, who are interested in e-Learning, are experienced in ICT and although they all use mobile devices in their everyday life, only a small percentage of them have adopted m-Learning in their teaching practice. There were 208 teachers who completed online a Mobile Learning Perception Scale questionnaire. Teachers’ views were in general positive and the more they use mobile technology in their classroom, the more they express positive perceptions. Four factors were identified (Communication, Delivery of teaching materials, Specialization, Teaching and Learning). ‘Specialization’ and ‘Teaching & Learning’ had higher values of average mean, in comparison to the other two factors. This finding indicates that secondary school teachers trust m-learning adequacy for teaching lessons of their specialization more than they do for communication purposes or delivery of teaching materials.